2018
DOI: 10.1016/j.anihpc.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The derivative nonlinear Schrödinger equation on the half line

Abstract: We study the initial-boundary value problem for the derivative nonlinear Schrödinger (DNLS) equation. More precisely we study the wellposedness theory and the regularity properties of the DNLS equation on the half line. We prove almost sharp local wellposedness, nonlinear smoothing, and small data global wellposedness in the energy space. One of the obstructions is that the crucial gauge transformation we use replaces the boundary condition with a nonlocal one. We resolve this issue by running an additional fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…where G(u), p i and q i are defined in ( 8)-( 10). To bound the first component of Φ, we use (11) to obtain…”
Section: Now We Verify the Continuity Thatmentioning
confidence: 99%
See 2 more Smart Citations
“…where G(u), p i and q i are defined in ( 8)-( 10). To bound the first component of Φ, we use (11) to obtain…”
Section: Now We Verify the Continuity Thatmentioning
confidence: 99%
“…Nevertheless, it is not a priori clear if different extensions of initial data produce the same solution on R + . We state an extension argument in [11]:…”
Section: Now We Verify the Continuity Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then the unconditional well-posedness for NLS was further improved, see [16,23,24,36,41] and studied for various other nonlinear dispersive PDEs, see e.g. [3,63] for KdV, [40,45,47,41] for the modified KdV equation, [13,50] for the derivative NLS equation, and [35] for the periodic modified Benjamin-Ono equation.…”
Section: Introductionmentioning
confidence: 99%
“…The initial boundary value problem for (1.5) in the quarter plane (x, t) ∈ R 2 | x ≥ 0, t ≥ 0 is overdetermined in the sense that the Dirichlet and Neumann boundary values at x = 0 cannot both be independently prescribed for a well-posed problem. Indeed, in [9] it was shown that the Dirichlet initial boundary value problem for (1.5) is locally well-posed in H s ([0, ∞)) for any s ∈ 1 2 , 5 2 , s = 3 2 , with given initial data q(x, 0) = g(x) and Dirichlet boundary data q(0, t) = h(t). In particular, for any g ∈ H s ([0, ∞)) and h ∈ H…”
Section: Introductionmentioning
confidence: 99%